Methodological Guide for Improving Risk Management Using the HAZOP Method Applied to Multifamily Housing Projects - Muedas, Anthony Enrique Calderon (2025)
Construction projects carried out using traditional methods involve different risks that are not anticipated or were not considered during the planning of multifamily housing projects. According to various studies, the absence of a risk management plan leads to project delays, poor project performance, and stakeholders’ dissatisfaction with project delivery. Therefore, this study provides a set of procedures for risk management in the planning stage of multifamily housing projects based on the method called Hazard and Operability Study (HAZOP), which identifies risks that may cause problems in project operations. The contribution of this research is to demonstrate that the method can improve risk management in multifamily housing projects in the province of Huancayo.